2000
DOI: 10.1002/(sici)1097-0223(200005)20:5<417::aid-pd816>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Apparent confined placental mosaicism of trisomy 16 and multiple fetal anomalies: case report

Abstract: Trisomy 16 is frequently found confined to the placenta (confined placental mosaicism (CPM)), with a structurally normal fetus. In some cases of trisomy 16, the fetus has uniparental disomy for chromosome 16 (UPD16) which is associated with intrauterine growth restriction (IUGR) and fetal anomalies. We report a case of apparent confined placental mosaicism for trisomy 16, using standard cytogenetic techniques, but with multiple fetal abnormalities including congenital diaphragmatic hernia in which there was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
(20 reference statements)
0
7
0
Order By: Relevance
“… 1 van Dooren et al 2003, 2 Johnson et al 2000, 3–11 Watt 1917, McCredie and Reid 1978, Brossard et al 1987, Cunniff et al 1993, Jelsema et al 1993, Pankau and Janig 1993, Bozner et al 1995, Marino et al 2002, 12,13 Czeizel and Losonci 1987, Genuardi et al 1994, 14–16 Gershoni‐Baruch et al 1990, Bird et al 1994, Devriendt et al 1999, 17 Holmes et al 1995, 18–21 Kunze et al 1979, Patel et al 1997, Han et al 2000, Van Allen and Myhre 1991, 22 Lipson et al 1993, 23–28 Frias and Felman 1974, McCredie and Reid 1978, Gugliantini et al 1984, Bamforth et al 1992, St Charles et al 1993, Hou and Wang 1999, 29–31 Poidevin 1953, Gouw et al 1985, Barr 1987, 32 Evans et al 1993, 33 Reid and Huff 1990, 34 Uygur et al 2004, 35 Halal et al 1980, 36 Ullrich and Bohm 1977, 37 St Charles et al 1993, 38–40 Lerone et al 1992, Froster et al 1996, Wallerstein et al 1997, 41–53 Schulz and Niemann 1971, Holzgreve et al 1984, Stanley et al 1984, Schinzel 1990, Rodriguez et al 1992, Czeizel et al 1994, Saal and Bulas 1995, Pivnick et al 1998, Heinonen 1999, Herman and Siegel 2001, Youn and Toriello 2003, Falcon et al 2004, and Oner et al 2004. …”
Section: Resultsmentioning
confidence: 99%
“… 1 van Dooren et al 2003, 2 Johnson et al 2000, 3–11 Watt 1917, McCredie and Reid 1978, Brossard et al 1987, Cunniff et al 1993, Jelsema et al 1993, Pankau and Janig 1993, Bozner et al 1995, Marino et al 2002, 12,13 Czeizel and Losonci 1987, Genuardi et al 1994, 14–16 Gershoni‐Baruch et al 1990, Bird et al 1994, Devriendt et al 1999, 17 Holmes et al 1995, 18–21 Kunze et al 1979, Patel et al 1997, Han et al 2000, Van Allen and Myhre 1991, 22 Lipson et al 1993, 23–28 Frias and Felman 1974, McCredie and Reid 1978, Gugliantini et al 1984, Bamforth et al 1992, St Charles et al 1993, Hou and Wang 1999, 29–31 Poidevin 1953, Gouw et al 1985, Barr 1987, 32 Evans et al 1993, 33 Reid and Huff 1990, 34 Uygur et al 2004, 35 Halal et al 1980, 36 Ullrich and Bohm 1977, 37 St Charles et al 1993, 38–40 Lerone et al 1992, Froster et al 1996, Wallerstein et al 1997, 41–53 Schulz and Niemann 1971, Holzgreve et al 1984, Stanley et al 1984, Schinzel 1990, Rodriguez et al 1992, Czeizel et al 1994, Saal and Bulas 1995, Pivnick et al 1998, Heinonen 1999, Herman and Siegel 2001, Youn and Toriello 2003, Falcon et al 2004, and Oner et al 2004. …”
Section: Resultsmentioning
confidence: 99%
“…Down syndrome is the most frequently occurring aneuploidy identified in children with a Morgagni hernia [22]. Other aneuploidies infrequently described with CDH include trisomy 9 [23], trisomy 16 [24], trisomy 22 [25], mosaic trisomy 2 [15], and mosaic trisomy 8 [7]. Sex aneuploidies including Turner syndrome (45,X) [10] and trisomy X (46,XXX) [6] have also rarely been described with CDH.…”
Section: Geneticsmentioning
confidence: 99%
“…The molecular breakpoints were not provided. There is also a report of a fetus with a right‐sided diaphragmatic hernia and mosaic trisomy 16 . To our knowledge, our patient is only the second report of partial trisomy 16p and diaphragmatic hernia.…”
mentioning
confidence: 51%
“…There is also a report of a fetus with a right-sided diaphragmatic hernia and mosaic trisomy 16. 4 To our knowledge, our patient is only the second report of partial trisomy 16p and diaphragmatic hernia. Wat et al recently reported two cases of syndromic CDH with a de novo 16p11.2 microdeletion detected by CMA.…”
mentioning
confidence: 69%